Review of shell-and-tube heat exchanger fouling and corrosion in geothermal power plant service - Ellis, P. F., II (Radian Corpration, 1983)
Heat exchangers for hot geofluid/working substance vaporizers for binary power plants are considered. A brief description of the physical test apparatus and the geofluid chemistry for each of the several heat exchanger tests is presented. The fouling data developed from these tests are summarized, in most cases presenting a mathematical expression for the increase in fouling factor with time. The materials performance data developed from these same tests are explored. The performance of shell-and-tube heat exchangers used as condensers and ancillary coolers in the power plant heat rejection system is considered.